2021
DOI: 10.1542/hpeds.2021-005877
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of UTIs in Infants <2 Months: A Living Systematic Review

Abstract: FRCPC a,b,d THE INSIGHTSCOPE TEAMCONTEXT: Urinary tract infections (UTIs) are the most common bacterial infections in infants <2 months of age. However, there are no clear guidelines on the appropriate duration of antibiotics in this age group. OBJECTIVE:In this living systematic review, we compared different durations of parenteral antibiotics (#3 vs >3 days) in neonates and young infants (<2 months) with UTIs. The secondary objective was to compare different durations of total antibiotic courses (#10 vs >10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…4 For instance, in infants with bacteremic UTI, outcomes are generally excellent despite a wide range in length of stay and duration of parenteral antibiotics. [17][18][19] Additional studies on CAP found that increased resource utilization including blood culture collection, leads to longer length of stay, with no data to support improved benefit. 20,21 Numerous studies, including several recent Pediatric Health Information System database studies, reveal high blood culture collection rates among these three diagnoses, with significant variability noted across hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 For instance, in infants with bacteremic UTI, outcomes are generally excellent despite a wide range in length of stay and duration of parenteral antibiotics. [17][18][19] Additional studies on CAP found that increased resource utilization including blood culture collection, leads to longer length of stay, with no data to support improved benefit. 20,21 Numerous studies, including several recent Pediatric Health Information System database studies, reveal high blood culture collection rates among these three diagnoses, with significant variability noted across hospitals.…”
Section: Introductionmentioning
confidence: 99%
“… 4 For instance, in infants with bacteremic UTI, outcomes are generally excellent despite a wide range in length of stay and duration of parenteral antibiotics. 17 19 Additional studies on CAP found that increased resource utilization including blood culture collection, leads to longer length of stay, with no data to support improved benefit. 20 , 21 …”
Section: Introductionmentioning
confidence: 99%